Absence-Free Vision: An Intelligent Classroom Attendance System with Facial Recognition - Velasquez Caceres, Samuel David (2024)
Attendance taking is a fundamental process in educational environments, but in Peru, there has been a lack of technological advancements in this area, resulting in disadvantages such as delays and human errors. Therefore, the objective of this research project is to propose a facial recognition system for attendance taking in university classrooms using cameras and artificial intelligence based on machine learning. To achieve this objective, the VDI 2206 design methodology is employed, which allows for establishing project requirements and conducting an initial design. Electronic models will be created and integrated into the proposed system. As a result, a detailed electrical diagram, a flowchart of the facial recognition process, a programming model for accurate student identification, and an implementation model in a real-world environment are expected to be obtained. The proposed system aims to optimize and streamline the attendance taking process in university classrooms, eliminating the need for manual intervention and minimizing errors. It is anticipated that this efficient and accurate solution will enhance academic management and the overall educational experience. In conclusion, this research project focuses on developing a facial recognition system for attendance taking in university classrooms within the Peruvian context. By utilizing advanced technologies and the VDI 2206 design methodology, the aim is to achieve an efficient and reliable system that optimizes the attendance taking process and contributes to an enhanced educational experience.